DAMPAK GAME ONLINE TERHADAP MOTIVASI BELAJAR MAHASISWA JURUSAN SOSIOLOGI FISPOL UNSRAT - Ondang, Gilbert Luis; Mokalu, Benedicta J.; Goni, Shirley Y. V. I. (HOLISTIK, Journal Of Social and Culture, 2020)
The development of science and technology gave birth to a variety of new discoveries, both in the field of science and technology. One of the results of new discoveries in the field of technology is the presence of online games. Online Games are electronic and visual based games, online games are also played using electronic visual media. The online game is very closely related to the attitude and morals and language used. Online games are an alternative choice for students when they are bored and tired of studying. But without realizing it, online games turned out to have an impact on players both positive, negative impacts and motivation to learn in college.This study aims to find out more about how the impact of online games on learning motivation in students who are in the Department of Sociology, Faculty of Mathematics and Natural Sciences. This study uses qualitative research methods and data collection techniques through observation, interviews and documentation. The theory used as an analysis tool for this research is Max Weber's social action.From the results of this study it was found that the game or game becomes very influential, when only used unilaterally. This means that it is not balanced by valuable activities, so it only has a negative impact, typically by students. Students have high competence in education, but if the game defeats the main activity, then this of course has an adverse effect on motivation to learn.Keywords: Impact; Online game; Motivation to learn